Optimisation of Preparation and the Characterisation of Microparticles from Sorghum Dried Distillers Grain with Solubles Protein - Zahoor, Umar (Curtin University, 2022)
Dried distillers grain with solubles (DDGS) kafirin is a hydrophobic protein by-product of ethanol production from sorghum grain. It is of great interest for its environmental and economical viabilities. This thesis reports the isolation and characterisation of DDGS kafirin and the optimised preparation of DDGS kafirin microparticles. The DDGS kafirin contained altered structural functionality to that of grain kafirin and optimised preparation supports its suitability as a micro-encapsulating agent for use in biomaterial production.